Notas históricas sobre el centralismo institucional chileno - Tagle, Matías (Revista EURE - Revista de Estudios Urbano Regionales, 1985)
This author examines some institutional and juridical issues that tend to demonstrate the continuous lack of political will of the directive class of the country for seriously attempting to spread the political power centered in the capital. It could be concluded that centralism is a sort of inherent cultural feature, and therefore very difficult to change.